Methodology for deriving multihazard factors for design base shear of buildings for wind and earthquake hazard for Peninsular India - Arunachalam, S.; Kamatchi, P.; Raju, K. Rama; Anoop, M.B.; Rao, K. Balaji; Harikrishna, P.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Recently there is an increased awareness about the probability based design which involves the knowledge about risk level associated with more than one hazard cumulatively known as multihazard. No systematic study is reported towards deriving the design force for multihazard based design. In this paper, a methodology has been proposed, to derive the multihazard factors for base shear for any given return period for wind and earthquake which are derived based on the existing knowledge about the mean annual rate of exceedance of wind and earthquake for a given region. Peninsular India is susceptible for high wind hazard due to the proximity of coast and moderate seismic hazard. Hence the proposed methodology is demonstrated by deriving multihazard factors for base shear for a twenty storey building for different cities of peninsular India viz., Chennai, Bangalore, Mumbai, Ahmedabad, Idukki and Visakhapatnam for wind and earthquake hazard. The sensitivity of multihazard base shear for different terrain categories (Category II and Category III) for wind load and for different site classes (site class C, D, E) for earthquake is studied. The proposed methodology provides a scientific platform for development of multihazard based design.